University's unique constituency : the non-campus countries. - STEELE, Beverley (1993)
Examines the services offered to the non-campus countries. Suggests that the outreach programmes need to be evaluated and upgraded to form a comprehensive package of distance education programmes, which will allow non-campus countries to access similar programmes to those offered to the campus countries.